2015
DOI: 10.1589/jpts.27.2807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sitting time associated with media consumption on physical activity patterns and daily energy expenditure of Saudi school students

Abstract: [Purpose] This study was performed to assess the effect of daily sitting time during media consumption on physical fitness, total energy expenditure (TEE), and body composition indices of Saudi school children. [Subjects and Methods] A total of 180 healthy Saudi school students (8–18 years) were included in this study. Sitting time, total energy expenditure, and levels of physical activity were evaluated with pre-validated internet based questionnaires. Body composition indices were evaluated using anthropomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
3
15
0
1
Order By: Relevance
“…Al-Agha et al concluded that children spending more than 2 hours of watching TV are associated with increased BMI [51]. A recent study done by Alghadir et al reported that children with moderate and active physical scores demonstrated less sedentary behavior (TV viewing and computer usage), lower body composition values, and higher total energy expenditure than sedentary or mild activity level participants [24]. Apart from health, sedentary behavior can have a profound impact on academics, motor skills and overall quality of life.…”
Section: Sedentary Behavior Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Agha et al concluded that children spending more than 2 hours of watching TV are associated with increased BMI [51]. A recent study done by Alghadir et al reported that children with moderate and active physical scores demonstrated less sedentary behavior (TV viewing and computer usage), lower body composition values, and higher total energy expenditure than sedentary or mild activity level participants [24]. Apart from health, sedentary behavior can have a profound impact on academics, motor skills and overall quality of life.…”
Section: Sedentary Behavior Characteristicsmentioning
confidence: 99%
“…In children and teens, BMI is age-and sex-specific and is often referred to as BMI-for-age. The body mass index has also been found to be related to total percentage of body fat in both boys and girls which can be influenced by genetic predisposition and environmental factors [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recent local studies highlight that several known risk factors for childhood obesity are particularly common in Saudi children. This includes high consumption of fatty foods and carbonated drinks in school and cafeterias (Alghadir et al ., ) as well as sedentary lifestyle secondary to media consumption (Alghadir et al ., ). The gender difference in physical activity confirms the previous finding of Al‐Sobaye et al .…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the longer young people sat down to watch TV or to play computer games, the greater the decrease in total energy consumption, whereas BMI and body fat increased to higher levels12 ) ; the study was conducted in 180 young students from Saudi Arabia (males and females). The same study showed that 67.5% of the highly obese patients included adults who performed little physical activity and worked in a sitting position on a sofa or a chair13 ) .…”
Section: Discussionmentioning
confidence: 99%